Inter-reaction between Urban Space and Representation - Long Shi (New Horizons in Education and Social Studies Vol. 8, 2021)
Urban Space plays a vital part in the mutual construction between city and literary texts, the textual representations offer unique way to know the city likewise. When literary works gives urban imaginative reality, and in turn the urban changes promotes the turn of literary texts. It is the textuality that is taken as the constant mutual construction between urban and literature.